2016
DOI: 10.2215/cjn.03710416
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Pathology in Dent Disease and Its Association with Kidney Function

Abstract: These associations suggest a potential role for glomerular pathology, specifically involving the podocyte, in disease progression, which deserves further study. Furthermore, Dent disease should be suspected in boys and men who have unexplained proteinuria with focal global glomerulosclerosis and segmental foot process effacement on renal biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 26 publications
4
47
0
Order By: Relevance
“…Focal global glomerulosclerosis, which is noted in 85% of Dent disease, is the predominant histopathologic finding, followed by effacement of foot processes. 13 Atypical presentations as seen in our patient have been reported with focal global glomerulosclerosis. 14 Making an accurate diagnosis of Dent disease is important to help avoid potentially toxic immunosuppressive medications.…”
Section: Quizsupporting
confidence: 69%
“…Focal global glomerulosclerosis, which is noted in 85% of Dent disease, is the predominant histopathologic finding, followed by effacement of foot processes. 13 Atypical presentations as seen in our patient have been reported with focal global glomerulosclerosis. 14 Making an accurate diagnosis of Dent disease is important to help avoid potentially toxic immunosuppressive medications.…”
Section: Quizsupporting
confidence: 69%
“…However, it was a pity that our younger brother did not have a renal biopsy, and therefore the severity of his tubular atrophy was unknown. There was a report on renal pathology and renal function, which showed that higher percentages of globally sclerotic glomeruli, foot process effacement, and interstitial inflammation were associated with a lower estimate of glomerular filtration rate (eGFR) at biopsy, whereas foot process effacement was associated with steeper annual eGFR decline (23). However, no correlation between phenotype and tubular atrophy has been reported in Dent disease.…”
Section: Resultsmentioning
confidence: 99%
“…To qualitatively prove the effectiveness and extendibility of our method, we show its extension to multi class detection by segmenting glomerular nuclei types [39,40], interstitial fibrosis and tubular atrophy (IFTA) [41,42], as well as differentiating sclerotic and non-sclerotic glomeruli [43] in mouse kidney and human renal biopsies. Figure 4 shows the glomeruli detection network from Figure 2 adapted for nuclei detection.…”
Section: Figure 2 H-ai-l Pipeline Performance: Glomerular Segmentatiomentioning
confidence: 98%